Design an Integrated Web-Based Plant Commodity Monitoring Information System - Yulianto, Achmad; Widya, Moh Anshori Aris (NEWTON: Networking and Information Technology, 2023)
In order to increase agricultural commodities in the Jombang Regency area to be higher, innovations are needed that can have a positive impact on the progress of the existing agricultural sector. One aspect that can support this progress is the existence of a plant commodity monitoring information system. The crop commodity monitoring system is a web-based application aimed at viewing and assessing the process of food crop growth systematically, starting from the planting period to the harvest period. From this system , historical crop data will be obtained, where these data can then be used as knowledge material for the Jombang Regency Agriculture Office in terms of policy making, such as the supply of seeds and fertilizer needs on subsidized and non-subsidized land, determination of planting periods, or predictions of agricultural products next year. In addition, this system also provides information related to plant conditions, plant age and instructions in determining plants to suit existing land. To realize this, the author designed and built an integrated web-based crop commodity monitoring information system on agricultural land. This research uses R&D (Research and Development) method. The test results using Black Box show that the functionality of this information system has been running well. The final result obtained from this study is that the system is more efficient and has comprehensive data than the old system that has been operating in the Jombang Regency Agriculture Office. Keywords: Agriculture, Plant Commodities, Monitoring, Web, Jombang Regency Agriculture Office